Comprensión de textos en inglés en estudiantes de quinto grado de secundaria en el Colegio Nacional de Iquitos y San Juan de Miraflores, San Juan Bautista 2020 - Motta Taminchi, Ali Eli (2022)
The objective of this research study was to compare fifth year students’ reading skills in English at Colegio Nacional Iquitos and San Juan de Miraflores secondary schools in San Juan Bautista district 2020 according to study shifts. The research type was comparative with field study, contemporary transectional, and univariate designs. The study population was made up by 670 students from both morning and afternoon shifts and a deterministic sample of 140: 74 students from the morning shift and 66 from the afternoon shift. The data gathering tool was a valid and a reliable reading comprehension test. Results show that the morning shift students obtained a slightly higher mean score compared to the afternoon shift students (11.211 > 9.867 out of 20). Similar results were obtained for its dimensions: Getting information (13.231 > 11.818); inferencing and interpreting information (10.419 > 9.136); evaluation of text content, context, and format (7.027 > 5.541). It is concluded that there is no statistically significant difference in reading comprehension in both groups as p-value = 0.081> ? 0.05.